The Duration of Protection from Azithromycin Against Malaria, Acute Respiratory, Gastrointestinal, and Skin Infections When Given Alongside Seasonal Malaria Chemoprevention: Secondary Analyses of Data from a Clinical Trial in Houndé, Burkina Faso, and Bougouni, Mali. (8th January 2021) - Phiri, Mphatso Dennis; Cairns, Matthew; Zongo, Issaka; Nikiema, Frederic; Diarra, Modibo; Yerbanga, Rakiswendé Serge; Barry, Amadou; Tapily, Amadou; Coumare, Samba; Thera, Ismaila; Kuepfer, Irene; Milligan, Paul; et al.
Abstract: Background: Mass drug administration (MDA) with azithromycin (AZ) is being considered as a strategy to promote child survival in sub-Saharan Africa, but the mechanism by which AZ reduces mortality is unclear. To better understand the nature and extent of protection provided by AZ, we explored the profile of protection by time since administration, using data from a household-randomized, placebo-controlled trial in Burkina Faso and Mali. Methods: Between 2014 and 2016, 30 977 children aged 3–59 months received seasonal malaria chemoprevention (SMC) with sulfadoxine-pyrimethamine plus amodiaquine and either AZ or placebo monthly, on 4 occasions each year. Poisson regression with gamma-distributed random effects, accounting for the household randomization and within-individual clustering of illness episodes, was used to compare incidence of prespecified outcomes between SMC+AZ versus SMC+placebo groups in fixed time strata post-treatment. The likelihood ratio test was used to assess evidence for a time-treatment group interaction. Results: Relative to SMC+placebo, there was no evidence of protection from SMC+AZ against hospital admissions and deaths. Additional protection from SMC+AZ against malaria was confined to the first 2 weeks post-administration (protective efficacy (PE): 24.2% [95% CI: 17.8%, 30.1%]). Gastroenteritis and pneumonia were reduced by 29.9% [21.7; 37.3%], and 34.3% [14.9; 49.3%], respectively, in the first 2 weeks postadministration. Protection against nonmalaria fevers with a skin condition persisted up to 28 days: PE: 46.3% [35.1; 55.6%]. Conclusions: The benefits of AZ-MDA are broad-ranging but short-lived. To maximize impact, timing of AZ-MDA must address the challenge of targeting asynchronous morbidity and mortality peaks from different causes. Abstract : Mass administration of azithromycin (AZ-MDA) alongside seasonal malaria chemoprevention in children in Burkina Faso and Mali has broad-ranging but short-lived benefits. To maximize impact, AZ-MDA must address the challenge of targeting asynchronous peaks in morbidity and mortality from different causes.